Penerapan PjBL Berbasis Ecoprint Untuk Meningkatkan Hasil Belajar Siswa Materi Mengamati Tulang Daun di Kelas IV Sekolah Dasar - Annisyah, Fitry; Mustika, Dea (Jayapangus Press, 2025)
Science, Environment, Technology, and Society (IPAS) learning in elementary schools is often considered less engaging because the approach remains theoretical and provides limited real-life experiences for students. This study aims to examine the planning, implementation, and evaluation of student learning outcomes through the application of the Project-Based Learning (PjBL) model integrated with ecoprint on the topic of observing leaf veins. The research employed a Classroom Action Research (CAR) design conducted in two cycles involving 28 fourth-grade students. The instruments used included teaching modules, teacher and student activity observation sheets, and learning achievement tests. The findings revealed a significant improvement in student learning outcomes. The average score increased from 57.1 in the pre-cycle to 63.43 in the first cycle and reached 87.64 in the second cycle. The percentage of students achieving mastery learning also rose from 64.28% in the pre-cycle to 85.71% in the second cycle. Furthermore, students’ creativity in producing ecoprint works improved by 78.6% compared to the initial condition, indicating higher engagement and enhanced creative thinking skills. It is concluded that the implementation of PjBL integrated with ecoprint is effective not only in improving student learning outcomes but also in fostering a contextual, active, and meaningful learning environment. Practically, this method can serve as an alternative strategy for teachers to integrate environmentally based creative projects into IPAS lessons, while also helping schools promote learning that supports the development of the Pancasila Student Profile. The novelty of this study lies in the integration of project-based learning with ecoprint techniques utilizing natural materials, which contributes not only to academic improvement but also to cultivating environmental awareness and creativity from an early age.